Self-health screening ability and satisfaction with the use of the Doctor at Home platform among people in primary care in Bangkok - Chunchote, Warapa; Jumnian, Malinee; Yana, Tassanee; Pongsanit, Kullatida; Sukmas , Chamaiporn (Thai Journal of Nursing, 2024)
This descriptive research aimed to evaluate the self- health screening ability and satisfaction with the use of Doctor at Home platform among people in primary care in Bangkok. A sample of 370 people including health volunteers, health workers and elderly people at a public health service center, workers of Nanyang company, and students of BangkokThonburi University, was purposively selected. Research tools were questionnaires on self - health screening ability and satisfaction with the use of Doctor at Home platform. The Cronbach’s alpha coefficients were 0.91 and 0.86 respectively. The data were analyzed using descriptive statistics. The research results were that the self- health screening ability of people were at the highest level (M = 3.32, SD = 0.61) and their satisfaction with the use of Doctor at Home platform were at a high level (M = 2.74, SD = 0.46).